Protective effect of interferon-? on carbon tetrachloride-induced nephrotoxicity - Dogukan, A; Akpolat, N; Çeliker, H; Ilhan, N; Bahçecioglu, IH; Günal, AI (Wichtig Editore, 2003)
Background: The aim of this study was to investigate the effect of chronic administration of interferon a 2b for the prevention of carbon tetrachloride (CC14)-induced oxidative stress and nephrotoxicity. Methods: Thirty rats were divided into three groups: control, CC14+placebo (CC14+P) and CC14+interferon-alpha 2b (CC14+INF). Control rats were treated with pure olive oil. The other rats were treated for seven weeks with subcutaneous injections of CC14 (0.15 mL/kg) in pure olive oil three times a week. Rats were killed at the end of the seventh week and renal histopathological examinations were done: specimens of renal tissue were obtained for investigating oxidative stress parameters, including malondialdehyde (MDA) and glutathione peroxidase (GSH-Px). Results: Tubular changes, glomerular hypercellularity, and capillary obliteration were significantly less in the CC14+INF group than with CC14+P (p<0.05) and the interstitial fibrosis score for the CC14+INF group was similar to the control group. However, the interstitial inflammation score was higher in the CC14+INF group than the control group (p<0.05). No change was observed in the CC14+P group. Renal MDA levels in the control and CC14+INF groups were significantly lower than the CC14+P group, while GSH-Px was significantly higher (p<0.001). There was no difference between the control and CC14+INF groups in oxidative stress markers (p>0.05). Conclusion: Administration of interferon-alpha 2b to CC14-treated rats prevented interstitial fibrosis, probably as a result of its antifibrogenic effect. It also reduced intrarenal oxidative stress in rats with CC14-induced nephrotoxicity.
Keywords: carbon tetrachloride; nephrotoxicity; interferon-alpha; oxidative stress